PENGARUH CAPITAL ADEQUACY RATIO, NON PERFORMING LOAN, LOAN TO DEPOSIT RATIO, RETURN ON ASSET, BIAYA OPERASIONAL TERHADAP PENDAPATAN OPERASIONAL DAN TOTAL ASSET TURNOVER TERHADAP PERUBAHAN LABA - Joko Susanto (Universitas Slamet Riyadi, 2015)
Purpose of this research to knows the effect of the Capital Adequacy Ratio, Non Performing Loan, Loan To Deposit Ratio, Return On Asset, BOPO And Total Asset Turnover to earnings changes. The population in this study is bank listed on the stock exchange the period of 2011-2013 with samples taken by purposive sampling as many as 31 banks. Data collection techniques used documentation. Data were analyzed used multiple linear regression analysis and, coefficient determination test, F test and t test. The results showed that Capital Adequacy Ratio has positive and significant effect to earnings changes. Non Performing Loan has negative and significant effect to earnings changes. Loan to Deposit Ratio has significant negative effect to earnings changes. Return On Assets has positive effect but not significant to earnings changes. BOPO has negative and significant effect to earnings changes. Total Assets Turnover has positive effect but not significant to earnings changes. The coefficient of determination are 0,494 means that influence of variable CAR, NPL, LDR, ROA, BOPO and TATO to earnings change amounted to 49,4 percent, while the remaining 50,6 percent is influenced by other variables not studied, for example, is the rate inflation, interest rate and current ratio. Keywords: Earnings Changes, CAR, NPL, LDR, ROA, BOPO, TATO